Oxotitanium-porphyrin for selective catalytic reduction of NO by NH3: A theoretical mechanism study - Rathawat Daengngern (2018)
© 2018 The Royal Society of Chemistry and the Centre National de la Recherche Scientifique. The reaction mechanism of the selective catalytic reduction of NO by NH3 (NH3-SCR) on an oxotitanium-porphyrin catalyst was systematically investigated by using density functional theory calculations with the M06L functional. The reaction was proposed to follow the nitrite mechanism over the two forms of active sites; the oxotitanium-porphyrin Lewis acid site (TiO-por) and the Brønsted acid site (TiOH-por). The reaction path consisted of (i) nitrite formation, (ii) NH3 oxidation, (iii) formation of NH2NO and NHNOH intermediates, and (iv) N2 and H2O product formation. The obtained calculations showed that the formation of the NHNOH intermediate was the rate determining step for both active sites with the energy barriers (Ea) of 32.2 and 36.2 kcal mol-1 for the Lewis and Brønsted acid sites, respectively. It is worth noting that the activation energy for NHNOH formation over the oxotitanium-porphyrin active sites was found to be in the same range as that of vanadium oxide cluster models. Furthermore, the product formations of N2 and H2O over the Lewis and Brønsted acid sites of oxotitanium-porphyrin were exothermic processes with reaction energies (Er) of -67.1 and -39.0 kcal mol-1, respectively. Thus, in conclusion, the oxotitanium-porphyrin could theoretically act as an alternative catalyst for NH3-SCR of NO and it would be challenging to test it in experimental studies.